2004
DOI: 10.1097/01.icl.0000138714.96401.2b
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Tear Volume (by Tear Meniscus Height and Phenol Red Thread Test) and Tear Fluid Osmolality Measures in Non-Lens Wearers and in Contact Lens Wearers

Abstract: Even contemporary contact lens wear can have a small but measurable impact on the precorneal tear film osmolality or volume. The changes are internally consistent and, overall, support the idea that the PRT test provides a useful measure of tear meniscus volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 20 publications
4
52
4
Order By: Relevance
“…Previous studies measuring tear osmolarity in contact lens wearers demonstrated increased tear osmolarity during wear time [1,3,11,17]. Similar results with both hydrogel and silicone hydrogel daily disposable contact lenses were obtained in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies measuring tear osmolarity in contact lens wearers demonstrated increased tear osmolarity during wear time [1,3,11,17]. Similar results with both hydrogel and silicone hydrogel daily disposable contact lenses were obtained in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Tear volume is distributed across three continuous compartments: the cul-de-sac, the conjunctival tear menisci, and the preocular tear film, and it depends on the rates of tear production, drainage, and evaporation. It has been reported that tear meniscus variables, such as height, width, cross-sectional area, and meniscus curvature are useful for the diagnosis of dry eye [13][14][15][16][17][18][19]. It is reasonable to use lower tear meniscus parameters as objective indicators of tearfilm status, since Wang et al [20] showed that upper and lower tear menisci have almost identical volume in healthy eyes.…”
Section: Introductionmentioning
confidence: 97%
“…Generally more than one objective test is needed to diagnose the condition, and to date there is no rigorous standard series of tests for clinicians to follow. For example, the phenol red thread (PRT) test is an index of tear production [8][9][10] , while tear break-up time assesses the stability of the tear film [8,10] . The large variety of available tests has led to widespread differences in the diagnosis of dry eye and the prevalence of their use in clinical practice, as revealed by a web-based questionnaire [11] .…”
Section: Introductionmentioning
confidence: 99%